Inventory, characterization and monitoring - Tixier-Boichard, M.; Ayalew, W.; Han Jianlin (Wageningen University & Research, 2008)
Inventory of species and breeds, their population sizes, geographic distribution and possibly their genetic diversity is generally undertaken as a first step in any national programme for the management of animal genetic resources for food and agriculture. The primary purpose of such an assessment is to document the current state of knowledge in terms of a population's ability to survive, reproduce, produce and provide services to farmers. Starting an inventory requires some knowledge of the inventory items and their characteristic attributes. Inventory and characterization are, therefore, complementary processes, in which the characterization step provides the baseline information as well as the criteria that will be used to establish and update the inventory. Characterization provides data on present and potential future uses of the animal genetic resources under consideration, and establishes their current state as distinct breed populations and their risk status. As use and management of animal genetic resources are dynamic processes, monitoring the status of a population has to be done on a regular basis. Thus, risk status indicators for use during the monitoring process need to be defined following the inventory and characterization steps. This paper discusses methods and criteria currently available, from research and past experience, for inventory, characterization and monitoring of animal genetic resources, with the view to assist in the Development of a more comprehensive framework. Particular consideration is given to emerging tools and technologies. The scope of the review includes all livestock species and their wild ancestors and wild related species. Examples focus on cattle, sheep, goats, pigs and chickens.